Analysts’ Incentives to Overweight Management Guidance When Revising Their Short-Term Earnings Forecasts - Feng, Mei; McVay, Sarah (The Accounting Review, 2010)
ABSTRACT: We document that, when revising their short-term earnings forecasts in response to management guidance, analysts wishing to curry favor with management weight the guidance more heavily than predicted, based on the credibility and usefulness of the guidance. This overweighting of guidance is present prior to equity offerings and other events that could lead to investment banking business. Although analysts sacrifice their forecast accuracy by overweighting management guidance, they appear to benefit, on average, by subsequently gaining the underwriting business for their banks. Thus, while analysts wishing to please managers are optimistic in their long-term earnings forecasts, they take their cue from management when determining their short-term earnings forecasts.